Synergistic anti-inflammatory effect of NSAIDs plus B vitamins administered pre and postoperatively in third molar surgery: randomized clinical trial - Pérez-Jimenez, Vanessa Roxana; Chumpitaz-Cerrate, Victor; Chávez-Rimache, Lesly; Moreno-Villalobos, David Erik; Rodríguez-Flores, Arturo Alberto; Franco-Quino, Cesar Ivanovich; Erazo-Paredes , Carlos Humberto (Brazilian Dental Science, 2022)
Objective: The aim of the present study was to evaluate the synergistic anti-inflammatory effect of Non-steroidalanti-inflammatory drugs (NSAIDs) plus B vitamins administered pre and postoperatively in surgeries of impactedmandibular third molars. Material and Methods: Double-blind randomized clinical trial, sixty-six patients participatedand were randomized into 2 groups. The control group was administered meloxicam 15 mg intramuscularly plusplacebo orally and to the experimental group, meloxicam 15 mg intramuscularly plus vitamins B [B1, B6, andB12] orally; both treatments were administered preoperatively. The anti-inflammatory effect was evaluated bypain intensity, facial swelling (facial contour measurements), and mouth opening (distance between the upperand lower incisors) during the post-surgical phase. Student’s t-test was performed for independent samples.Results: In all the evaluated times (1 hour, 6 hours, 12 hours, 24 hours, 2 days, and 3 days after the end of thesurgery) the experimental group presented a significantly lower intensity of pain compared to the control group(p0.05). Conclusion: In the present study, the administration of NSAIDs plus B vitamins (B1, B6,B12) produced lower intensity of pain compared to the administration of only NSAIDs. Nevertheless, swellingand mouth opening were similar in all evaluations for both study groups.KEYWORDSVitamin B complex; Inflammation; Meloxicam; Molar, third; Pain.